Between Science, Movement, and Democracy: Scientists for Future in the Politics–Society Interface - Laura Herzog; Andrea Lenschow; Jan Pollex (Politische Vierteljahresschrift, 2023)
In the midst of the recent wave of climate activism, a~group of scientists formed the initiative Scientists for Future (S4F) to support the Fridays for Future movement and emphasise the scientific evidence their activism is based on. While scientists have participated in policymaking by taking roles as advisers to policymakers in the past, forming a~social movement is an unprecedented form of communicating scientific evidence. In this contribution, we assume that the S4F initiative aims to voice dissatisfaction both with prevalent decision-making processes and with the substance of these decisions. Using novel data from a~survey conducted among members of this movement in the summer of 2021, we investigated their motivations and perspectives on the role of scientists in democratic processes and their attitudes about a~reformist or more radical pathway towards a~climate-neutral society and sustainable development. Our analysis shows that the majority of S4F members support democratic reforms rather than fundamental systemic change. Furthermore, most respondents show signs of a~conviction that scientific expertise should take a~superior role in climate policy rather than make room for wide participatory practices. Overall, the S4F is aimed at the diversification of political arenas to raise the impact of scientific knowledge in environmental and climate policymaking.
Keywords: 320; Climate activism; Social movement; Scientists for Future; Ecological democracy; Environmental democracy; Policy experts; Klimaaktivismus; Soziale Bewegung; Scientists for Future; Ökologische Demokratie; Umweltdemokratie; Politikexperten